1994
DOI: 10.7748/ns.8.26.27.s39
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen mask or nasal catheter? An analysis

Abstract: In pursuit of cost-efficiency without compromising standards of patient care, a study was undertaken to compare the performances of a medium concentration facemask and a nasal catheter, by measuring the oxygen saturation levels of 40 post-operative patients. Statistical analysis revealed that when oxygen is delivered at 3 litres/minutes, there is no significant difference between the performances of these systems. Patients and nurses indicated a preference for the nasal catheter compared with the facemask. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They not only found that patients maintained adequate oxygen saturations with cannulae, but that patients also kept the device in place. In another study, English and Brown found that the sex of the patient had no influence on the oxygen saturation scores when comparing the face mask and nasal catheter 5 . Hudes et al studied patients who were desaturated on arrival in the recovery ward 6 .…”
Section: Review Of the Researchmentioning
confidence: 99%
“…They not only found that patients maintained adequate oxygen saturations with cannulae, but that patients also kept the device in place. In another study, English and Brown found that the sex of the patient had no influence on the oxygen saturation scores when comparing the face mask and nasal catheter 5 . Hudes et al studied patients who were desaturated on arrival in the recovery ward 6 .…”
Section: Review Of the Researchmentioning
confidence: 99%
“…2007). Although there is little recent published work, researchers have evaluated the effectiveness of low‐flow oxygen therapy devices in terms of satisfactory blood oxygen concentrations, usually measured by pulse oximetry (SpO 2 ), or arterial blood gas analysis (ABG) (English & Brown 1994, McBrien & Sellers 1995, Eastwood et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Those who receive oxygen via a low-flow device typically have minimal respiratory distress and can maintain adequate ventilatory patterns (Eastwood et al 2007). Although there is little recent published work, researchers have evaluated the effectiveness of low-flow oxygen therapy devices in terms of satisfactory blood oxygen concentrations, usually measured by pulse oximetry (SpO 2 ), or arterial blood gas analysis (ABG) (English & Brown 1994, McBrien & Sellers 1995, Eastwood et al 2008. Some earlier researchers have described patterns of supplemental oxygen use (Albin et al 1992, Gravil et al 1997 or the impact of device factors, such as size, shape and fit on oxygen delivery and patient oxygenation (Milross et al 1989, Ooi et al 1992.…”
Section: Introductionmentioning
confidence: 99%